Using AlphaFold-Multimer to study novel protein-protein interactions of predation essential hypothetical proteins in Bdellovibrio - Abulude, Ibukun John; Luna, Isabel Cristina Rodríguez; Varela, Alejandro Sánchez; Camilli, Andrew; Kadouri, Daniel E.; Guo, Xianwu (Frontiers in Bioinformatics, 2025)
Bdellovibrio bacteriovorus is the most studied member of a group of small motile Gram-negative bacteria called Bdellovibrio and Like Organisms (BALOs). B. bacteriovorus can prey on Gram-negative bacteria, including multi-drug resistant pathogens, and has been proposed as an alternative to antibiotics. Although the life cycle of B. bacteriovorus is well characterized, some molecular aspects of B. bacteriovorus-prey interaction are poorly understood. Hypothetical proteins with unestablished functions have been implicated in B. bacteriovorus predation by many studies. Our approach to characterize these proteins employing Alphafold has revealed novel interactions among attack phase-hypothetical proteins, which may be involved in less understood mechanisms of the Bdellovibrio attack phase. Here, we overlapped attack phase genes from B. bacteriovorus transcriptomic data sets and from transposon sequencing data sets to generate a set of proteins that are both expressed at the attack phase and are necessary for predation, which we termed Attack Phase Predation-Essential Proteins (AP-PEP). By applying Markov Cluster Algorithm and AlphaFold-Multimer to analyze the protein network and interaction partners of the AP-PEPs, we predicted high-confidence protein-protein interactions and two structurally similar but unique novel protein complexes formed among proteins of the Bd2209-Bd2212 and Bd2723-Bd2726 operons. Furthermore, we confirmed the interaction between hypothetical proteins Bd0075 and Bd0474 using the Bacteria Adenylate Cyclase Two-Hybrid system. In addition, we confirmed that the C-terminal domain of Bd0075, which contains Tetratricopeptide repeat motifs, participates principally in its interaction with Bd0474. This study revealed previously unknown cooperation among predation essential hypothetical proteins in the attack phase B. bacteriovorus and has paved the way for further work to understand molecular mechanisms of BALO predation processes.